Upaya Penurunan Angka Perkawinan Anak: Studi Kasus Di Kecamatan Nawangan Kabupaten Pacitan - Clearestha Nakita; Anjar Sri Ciptorukmi Nugraheni (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This research uses empirical legal research methods. This research aims to determine and analyze the urgency of efforts to reduce child marriage rates and efforts to reduce child marriage rates in Nawangan District. The results of the research show that the urgency of efforts to reduce the number of child marriages in Nawangan District is from a health perspective, an economic perspective, a psychological aspect and a legal perspective. Meanwhile, efforts to reduce the number of child marriages in Nawangan District are carried out through outreach and counseling carried out by the Head of Nawangan District with stakeholders, namely RT/RW heads, Village Heads, Community Health Centers, educational institutions, and Forkopimca.